Estimation of Indonesia's Energy Demand to 2030 and Alternatives Scenario to Reduce Oil Dependence - Dwi Atty Mardiana; RS. Trijana Kartoatmodjo; Sugiatmo Kasmungin (Purnomo Yusgiantoro Center, 2018)
The impacts of high dependence on oil on the economy have encouraged many countries to start eliminating or sharply reducing their dependence on oil consumption. As an oil importer as well as oil and gas producer country, Indonesia seeks to do the same thing by eliminating fuel subsidies, shifting to gas, and developing renewable energy. The oil price affects the economic and energy policies and impacts the efforts of reducing oil dependence. Using an econometric model of Indonesia’s energy that is constructed based on its energy balance model, this paper will examine factors that influence the oil demand in Indonesia. It will estimate the country’s energy needs from 2017 to 2030 and simulate various alternative strategies to deal with oil dependencies, such as an increase in the refinery capacity, and a shift from oil to gas in the transportation sector. This paper suggests that shifting from oil to gas in the transportation sector will be able to reduce oil dependency, while the alternative of increasing refinery capacity to 3 million barrel per day will be an opportunity to support greater short-term energy security and economic returns.